The Effect of Heat Flux on the Fire and Chemical Properties of Oak Wood (Quercus petraea) - Martin Zachar; Alena Párničanová; Danica Kačíková; Iveta Čabalová; Lucia Zacharová (BioResources)
Selected fire properties of oak wood (mass loss, burning rate, and charring rate) and its chemical composition (extraction substances, lignin, cellulose, hemicellulose) were assessed. Oak wood samples with dimensions of 50 × 40 × 50 mm (l × w × t) were thermally loaded by a heat flux of 15, 20, 25, and 30 kW·m-2, using a ceramic infrared heater with a power of 1000 W. At the given thermal loading, the mass loss ranged from 26% to 47%, whereas the burning rate ranged from 0.0365 to 0.0584%·s-1. The maximum thickness of charred layer was 20 mm, and the charring rate reached values from 0.65 to 0.87 mm·min-1, in a time interval of 1800 s. With increasing thermal loading, the content of extraction substances increased by 30% and the content of lignin increased slightly as well. In contrast, the content of hemicelluloses decreased by 10.3%. This indicates that hemicelluloses are the least thermally resistant wood component. The obtained results can be used as basic data for future testing using medium-sized tests. Subsequently, they can be compared with the input parameters for calculating the fire resistance of wooden constructions elements, which will be the subject of further research.